2022
DOI: 10.2528/pierm22020601
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of Reconfigurable Intelligent Surface in Cooperative Decode-and-Forward Relaying for Hybrid Rf/Fso Systems

Abstract: Reconfigurable intelligent surface (RIS) has been suggested as a promising solution to prevent wireless communication systems from transmission blockage. In this paper, the performance of reconfigurable intelligent surface in cooperative decode-and-forward relaying for hybrid radio frequency (RF)/free space optical (FSO) system is evaluated where parallel transmission of information occurs on the system downlink. In this network, the RF links in the system are assumed to follow Nakagami-m distributions while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Therefore, a study in [29] scrutinized a full-duplex (FD) relaying-based RF-FSO mixed system, revealing substantial performance enhancements achieved through the utilization of parallel RF/FSO links within an FD relaying channel. In [30], it was demonstrated that the RISaided mixed downlink system clearly performs better than the hybrid downlink system without RIS.…”
Section: A Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a study in [29] scrutinized a full-duplex (FD) relaying-based RF-FSO mixed system, revealing substantial performance enhancements achieved through the utilization of parallel RF/FSO links within an FD relaying channel. In [30], it was demonstrated that the RISaided mixed downlink system clearly performs better than the hybrid downlink system without RIS.…”
Section: A Background and Related Workmentioning
confidence: 99%
“…( 20)]. Therefore, the asymptotic representation for the lower bound of SOP 3 can be expressed as (30) where Φ p,q illustrates the qth-term…”
Section: Scenario−iiimentioning
confidence: 99%
“…Thus, the CDF equivalent end-to-end SNR of the ground user for the proposed network can be defined as [29,30]:…”
Section: Statistical Characteristics Of Equivalent Snrmentioning
confidence: 99%
“…However, the proposed system was not a relay-assisted communication. Also, the authors in [16] studied the performance of an RIS-aided cooperative hybrid FSO/RF network, but the relay mode was based on half duplex where the self-interference at the relay was negligible. Also, the foggy condition was not considered as channel impairments on the FSO link.…”
Section: Introductionmentioning
confidence: 99%